Application of Foam Mat Drying in the Making of Herbal Powder - Wiyono, Andi Eko; Mawaddah, Faireza; Mahardika, Nidya Shara (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The increasing demand for herbal raw materials in Indonesia is evidenced by data according to Riskesdas in 2010-2018 increased by 44.3%. The data also states that 59.12% of Indonesians still consume herbal medicine and 95.6% know the benefits of herbal medicine. The herbal drink consists of various spice mixtures. Commonly used spices consist of ginger, aromatic ginger and lemongrass. Ginger contains gingerol active compounds with antioxidant activity above vitamin E and α-tocopherol. Aromatic ginger contains phenol chemical compounds as antioxidants that are analgetic. Lemongrass contains bioactive compounds as antioxidants. Generally, herbal products are processed in liquid form so that they have a low shelf life, and are easily damaged and contaminated. Therefore, there is a need for innovation in making herbal drinks into powder with the foam mat drying method using a microwave. The process of making herbal powder is added with tween® 80 and maltodextrin. This study aims to determine the effect of foaming agents and fillers on the organoleptic and physicochemical characteristics of herbal powder, yield value, antioxidant activity and mass balance of the selected treatment. This study used RALF with 2 factors consisting of the ratio of fillers and foaming agents. This study used organoleptic test parameters and physicochemical tests. Results The determination of the selected treatment (organoleptic test) is analyzed for its mass balance and antioxidant activity. The results showed that the addition of the ratio of foaming agents and fillers had a significant effect on organoleptic and physicochemical test characteristics. The herbal powder selected based on the Spider Web test is an A1B2 treatment with a yield value of 11.85% and antioxidant activity of 69.6%. The calculated mass balance results in an efficiency value of no more than 1 (100%) and the largest mass loss in the drying process of 577.72 gr or 88.05% of the incoming material.